MICROCAPSULE-MANUFACTURING PROCESS AND MICROCAPSULES - IWAMOTO, TADASHI; YAMAUCHI, HIROSHI (2016)
The present invention aims to provide a method for producing microcapsules, wherein the method can control the particle size and produce microcapsules excellent in retentivity and releasability of a water-soluble core agent. The present invention also aims to provide a microcapsule excellent in retentivity and releasability of a water-soluble core agent. The present invention provides a method for producing microcapsules comprising the steps of: preparing an emulsion by dispersing an aqueous solution A obtained by dissolving at least an aqueous solvent-soluble polymer and a water-soluble core agent in an aqueous solvent in a non-polar solution B obtained by dissolving an emulsifier or a dispersant in a non-polar medium; and forming a core-shell structure in which the water-soluble core agent is covered with a shell containing the aqueous solvent-soluble polymer by heating the emulsion at a temperature of 20°C to 100°C and/or decompressing the emulsion at a pressure of 0.1 to 0.001 MPa to remove the aqueous solvent, the weight ratio of the aqueous solution A to the non-polar solution B being 1/10 to 1/1.